The Usefulness of Combined B Mode and Doppler Ultrasonography to Guide Treatment of Appendicitis - Ohba, Go; Hirobe, Seiichi; Komori, Koji (European Journal of Pediatric Surgery, 2016)
Introduction We have succeeded in classifying the severity of appendicitis by evaluating the structure of the submucosal layer and blood flow in the appendix wall with ultrasonography (US). Here, we propose a new preoperative classification system to guide treatment strategy.Materials and Methods Between February 2005 and December 2011, a total of 440 acute appendicitis cases were diagnosed, and 407 met inclusion criteria for this study. US and Doppler findings were used to classify cases as Grade I, IIa, IIb, III, or appendiceal mass. Grades I and IIa were treated conservatively without antibiotics. Appendectomy for Grades IIb and III and interval appendectomy for appendiceal mass were performed.Results Of 407 cases, 38 were Grade I, 132 were Grade IIa, 130 were Grade IIb, 57 were Grade III, and 50 were appendiceal mass. Improvement occurred without antibiotics in 37 (97.3%) Grade I and 129 (97.7%) Grade IIa cases. Recurrence occurred postdischarge in 9 (23.6%) Grade I and 35 (26.5%) Grade IIa cases. All Grades IIb and III patients had gangrenous or phlegmonous appendicitis. There were no negative appendectomies.Conclusion Even if US findings reveal swelling or an irregular submucosal layer, when power Doppler identifies abundant blood flow, inflammation may improve spontaneously. Decreased appendiceal wall blood flow indicates irreversible necrotic change. Doppler and B-mode US used together improve acute appendicitis treatment.
Keywords: acute appendicitis; ultrasound; power Doppler ultrasonography